Systematic Analysis of the Amino Acid Residues of Human Papillomavirus Type 16 E7 Conserved Region 3 Involved in Dimerization and Transformation - Todorovic, Biljana (American Society for Microbiology, 2011)

(untitled)
The human papillomavirus (HPV) E7 oncoprotein exists as a dimer and acts by binding to many cellular factors, preventing or retargeting their function and thereby making the infected cell conducive for viral replication. Dimerization of E7 is attributed primarily to the C-terminal domain, referred to as conserved region 3 (CR3). CR3 is highly structured and is necessary for E7's transformation ability. It is also required for binding of numerous E7 cellular targets. To systematically analyze the molecular mechanisms by which HPV16 E7 CR3 contributes to carcinogenesis, we created a comprehensive panel of mutations in residues predicted to be exposed on the surface of CR3. We analyzed our novel collection of mutants, as well as mutants targeting predicted hydrophobic core residues of the dimer, for the ability to dimerize. The same set of mutants was also assessed functionally for transformation capability in a baby rat kidney cell assay in conjugation with activated ras. We show that some mutants of HPV16 E7 CR3 failed to dimerize yet were still able to transform baby rat kidney cells. Our results identify several novel E7 mutants that abrogate transformation and also indicate that E7 does not need to exist as a stable dimer in order to transform cells.